A broad definition of agential power. Issue 1 (2nd January 2018) - Gilabert, Pablo
Abstract: Can we develop a definition of power that is satisfactorily determinate but also enables rather than foreclose important substantive scientific and normative debates about social and political life? I present a broad definition according to which agents have power with respect to a certain outcome (including, inter alia, the shaping of certain social relations) to the extent that they can voluntarily determine whether that outcome occurs. This simple definition generates a surprisingly complex agenda for substantive descriptive and normative inquiry. The proposed definition is partly developed through a critical engagement with Rainer Forst's important recent account of 'noumenal power.'